Wunderlich syndrome (spontaneous renal hematoma) as a cause of acute abdomen: a case report - Miranda, Militza Cerrillo; Pereyra Molina, Jose A.; Gonzalez, Flavio Hernandez; Vazquez Barrios, Carlos E.; Valmana, Osvaldo I. Guevara; Lara Becerra, Jose A. (International Journal of Research in Medical Sciences, 2021)
Spontaneous renal hemorrhage, also known as Wünderlich syndrome, is a rare condition that can be life-threatening and consists of the onset of sudden hemorrhage into the subcapsular and perirenal spaces. It can be lethal as it goes unnoticed and requires aggressive treatment. The entity lies mainly in neoplasms, the malignant ones being the most common. We present the case of a 63-year-old female patient with acute abdomen clinic, a diagnostic laparoscopy was performed and renal hematoma was evidenced as the cause of the symptoms. It was managed conservatively without any complications. We emphasize the importance of keeping in mind Wünderlich syndrome as a differential diagnosis to instigate early treatment for a better outcome.